Does menopause start earlier in smokers? Evidence from the Pro-Saude Study - Paula de Holanda Mendes; Eduardo Faerstein; Washington Leite Junger (Instituto Materno Infantil de Pernambuco, 2013)
OBJECTIVES: cigarette smoking has been the modifiable risk factor most consistently associated with earlier menopause. This preliminary study based on cross-sectional data aimed to analyze the association between smoking status and age of onset of menopause in a Brazilian population. METHODS: a cross-sectional study was carried out with 1,222 female employees of Rio de Janeiro university campuses aged over 35 years who were at risk of natural menopause. A Cox proportional hazards model was used to investigate the association between smoking status and age at the onset of menopause, adjusting for education, parity and alcohol consumption. RESULTS: current smokers showed a 56% increase in the risk of menopause, being 1.8 years younger at menopause onset compared with women who had never smoked. However, no differences were observed between former smokers and women who had never smoked. The adjusted median age at menopause was 49.5 years for current smokers and 51.3 years for women who had never smoked (p<0.05). CONCLUSIONS: the results suggest a deleterious but potentially reversible effect of smoking on the age of onset of menopause, which should receive greater attention in tobacco control efforts. Longitudinal analyses of this association will be carried out in the future in a follow-up study of this population.